Islamic Corporate Governance And Sharia Compliance On Financial Performance Sharia Bank In Indonesia - Umiyati Umiyati; Laila Maisyarah; Mustafa Kamal (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2020)
This study aims to reveal the influence of Islamic Corporate Governance (ICG) and Sharia Compliance on Financial Performance of Islamic Banks in Indonesia. Independent variables used are Islamic Corporate Governance (ICG) and Sharia Compliance with Islamic Income Ratio (IsIR), Profit Sharing Ratio (PSR) and Zakat Performing Ratio (ZPR) as the proxy. In contrast, the dependent variable used is Financial Performance with Return On Asset as the proxy. The population in this study is all Islamic Banks (BUS), registered in Bank Indonesia from 2014 to 2018. The sample was selected using a purposive sampling method. Total samples used in this study are 8 Islamic Banks with 5-year study periods. The analytical method used is data panel regression with the help of e-views 9.0. The result of this study indicates that the Islamic Corporate Governance (ICG) and Zakat Performing Ratio (ZPR) have significant effects on Islamic Banks Financial Performance. At the same time, Islamic Income Ratio (IsIR) and Profit Sharing Ratio (PSR) did not affect Islamic Banks Financial Performance.Penelitian ini bertujuan mengetahui pengaruh Islamic Corporate Governance dan Sharia Compliance terhadap Kinerja Keuangan Bank Umum Syariah di Indonesia. Variabel independen pada penelitian ini adalah Islamic Corporate Governance (ICG), dan Sharia Compliance dengan indikator Islamic Income Ratio (IsIR), Profit Sharing Ratio (PSR) dan Zakat Performing Ratio (ZPR), sedangkan variabel dependen adalah Kinerja Keuangan dengan indikator Return On Asset (ROA). Populasi dalam penelitian ini adalah seluruh Bank Umum Syariah di Indonesia periode 2014-2018. Sampel dipilih dengan menggunakan metode Purposive Sampling. Total sampel yang digunakan dalam penelitian ini sebanyak 8 BUS dengan 5 tahun periode penelitian. Metode analisis yang digunakan ialah metode regresi data panel, dengan alat analisis e-views 9.0. Hasil penelitian ini menunjukan bahwa Islamic Corporate Governance (ICG) dan Zakat Performing Ratio (ZPR) berpengaruh signifikan terhadap Kinerja Keuangan Bank Umum Syariah. Sedangkan Islamic Income Ratio (IsIR) dan Profit Sharing Ratio (PSR) tidak mempengaruhi Kinerja Keuangan Bank Umum Syariah.